A Purified Biflavonoid Extract From Selaginella moellendorffii Alleviates Gout Arthritis via NLRP3/ASC/Caspase-1 Axis Suppression - Zhang, Xueyan; Liu, Yingbo; Deng, Guangrui; Huang, Bisheng; Kai, Guoyin; chen, Keli; Li, Juan (Frontiers in Pharmacology, 2021)
Background: Activation of nucleotide oligomerization domain-like receptor protein 3 (NLRP3) inflammasome plays a key role in gout. Selaginella moellendorffii has been confirmed effective for the treatment of gout in hospital preparations. Flavonoids are the main effective components of this medicine. Whether the purified biflavonoid extract (TF) has any influence on the activation of NLRP3 inflammasome in gout remains unknown. Purpose: We aimed to investigate the effects of TF and its main constituent amentoflavone (AM) on NLRP3 inflammasome in vitro and their preventive effects on gout in vivo. Methods: LC-MS method was employed to investigate the chemical profile of TF. The cellular inflammation model and gout model were established by lipopolysaccharide (LPS) or monosodium urate (MSU) stimulation. The cell membrane integrality and morphological characteristics were determined by using Lactate dehydrogenase (LDH) assay kits, propidium iodide (PI) stain, and scanning electron microscopy (SEM). The inflammatory cytokines and NLRP3 inflammasome activation were determined by using enzyme-linked immunosorbent assay (ELISA), quantitative real-time polymerase chain reaction (RT-PCR), immunofluorescence staining, and western blotting. The effects of oral administration with TF and AM were examined in an acute gout mouse model induced by injection of MSU into footpads. The paw edema, inflammatory mediators, and histological examination (HE) were analyzed. Results: AM and robustaflavone were identified from TF. In cellular inflammation model, TF down-regulated the levels of nitric oxide (NO), TNF-α, and LDH, suppressed NLRP3 inflammasome-derived interleukin-1β (IL-1β) secretion, decreased caspase-1 activation, repressed mature IL-1β expression, inhibited ASC speck formation and NLRP3 protein expression. In an acute gout mouse model, oral administration of TF to mice effectively alleviated paw edema, reduced inflammatory features, and decreased the levels of IL-1β in mouse foot tissue. Similarly, the characteristic constituent AM was also able to down-regulated the levels of NO, TNF-α, and LDH, down-regulate the mRNA expression of IL-1β, TNF-α, caspase-1, and NLRP3. Besides, the foot thickness, lymphocyte infiltration, and IL-1β level were also prevented by AM. Conclusions: The results indicated that TF and its main constituent AM alleviate gout arthritis via NLRP3/ASC/Caspase-1 axis suppression.